PERAN PENGETAHUAN EKOLOGI SEBAGAI PEMEDIASI HUBUNGAN ANTARA KOMUNIKASI PEMASARAN TERPADU DAN KEPUASAN PELANGGAN - Hadi, Antonius Satria (Department of Management - Institut Shanti Bhuana, 2022)
The negative effect of greenhouse gas emissions that have an impact on environmental degradation causes pressure on the tourism sector and the accommodation industry. Besides being revived due to the effects of the Covid-19 pandemic, the industry is also faced with environmental awareness. This is the basis for doing this research. This study was conducted with the aim of examining the mediating effect of ecological knowledge between the relationship of integrated marketing communications with customer satisfaction. Respondents in this study were customers/visitors/guests who had stayed at hotels located in Yogyakarta. The sampling technique used in this study was purposive sampling with a total sample of 100 respondents. Hypothesis testing, confirmatory factor analysis test, validity test, and reliability test using SmartPLS 3 software. All hypotheses proposed in this study were accepted.